The relationship between soil and household dust metals and the impact on olfaction in children. (20th October 2021) - Renzetti, S; Placidi, D; Borgese, L; Cagna, G; Conversano, M; Patrono, A; Peli, M; Ranzi, R; van Thriel, C; Lucchini, RG
Abstract: Background: Through this study we aimed to test the association between the exposure to metals measured in soil, outdoor and indoor dust and olfactory function among children living close to ferromanganese alloy plants. Moreover, we investigated how metal concentrations vary with the distance from the plants and the relationships among the different environmental media. Methods: A total of 130 children between 6 and 13 years old were enrolled in the province of Brescia in Italy. The olfactory performance was assessed through the Sniffin' Sticks test. The concentration of 20 metals in dust and soil samples was determined through an X-ray fluorescence portable analyzer (p-XRF). Weighted Quantile Sum (WQS) regression was applied to test for the association between the multi-media environmental markers (MMEM) and olfactory function while restricted cubic splines were used to evaluate the relationship between metal concentrations and distance from the closest plant and deviation from the main wind direction. Results: WQS regression showed a negative significant association between the MMEM and the Sniffin' Sticks score (beta=-0.028; 95%CI -0.047, -0.009) identifying As, Fe, Rb, Pd, K and Pb as the elements with the higher weights. Except Rb, all elements together with Mn (one of the main elements released by the plants), showed a decreasing trend for soil and outdoor dust concentration at increasing distance from the source or at increasing deviation from the main wind direction. A positive association between outdoor and indoor dust and between soil and outdoor dust was also observed. Conclusions: This work highlights the risk of the exposure to metal mixtures on child olfactory function which is known to be associated with neurodegenerative diseases in older age. Moreover, this analysis can contribute in terms of public health policies assessing the risk of being exposed as a function of the distance from the plants and the deviation from the main wind direction. Key messages: Metal mixture concentration in dust is associated with decreased smell identification ability. Indoor metal concentrations can be affected by external source of exposure.